You Want More When You Have Something in Your Hand - Kim, Hakkyun; Han, Youngjee; Jeon, Eunmi (ASIA MARKETING JOURNAL, 2019)
In this research, two studies show that the bodily experience of holding objects in the hand is tied to the mental concept of acquiring material wealth. Holding objects in the hand (a) increased people’s desires for possessing fairly luxurious goods (Study 1) and (b) made people judge a controversial issue (e.g., “sweatshops” run by global companies) more favorably based on wanting to generate more wealth for individuals and society rather than on humanitarian concerns (Study 2). These results provide evidence that the bodily experience not only helps to represent an abstract concept but also can shape attitude and judgment congruent with the metaphor represented in the bodily experience.